Escribimos textos descriptivos utilizando conectores de adición - Ildefonso Zavaleta, Nilda Elizabeth (2019)
This sufficiency work has been prepared for children in the second grade of primary education of the Educational Institution “Rafael Narvaez Cadenillas” Of the city of Trujillo in 2019, with the theme “We write descriptive texts using connectors of addition”, in which he writes several texts in his mother tongue._x000D_ In the elaboration of the session, we have worked with the didactic processes of the area of Communication and with the capacity It uses conventions of the written language in an appropriate way infers and interprets information from the text and the performance writes around a topic. Group the ideas into sentences and develop them to expand the information, although sometimes you can reiterate unnecessarily. It establishes relationships between ideas for addition and sequence using some connectors incorporated into its frequently used vocabulary._x000D_ The strategies used were designed to promote the active and meaningful participation of all students._x000D_ It is intended at all times to awaken the interest and motivation of the student for the production of texts, since it is a very important area whose purpose is for students to develop communication skills.